Aesthetics Of Gamelan Geguntangan in Bali | Estetika Gamelan Geguntangan di Bali - Andika, I Made Dwi (GHURNITA: Jurnal Seni Karawitan, 2024)
The topic focused on in this article is the aesthetics of Gamelan Geguntangan in Bali. Gamelan Geguntangan is the material object of this research, while the formal object is the aesthetics contained in it. Gamelan Geguntangan is one of the gamelan variants still in Bali today and is a valuable Balinese artistic and cultural heritage. Gamelan Geguntangan has its charm because it is often used to accompany vocals performed by Arja dancers and by pesantian sekaa-sekaa in various regions in Bali. The basis for this initial understanding of aesthetics is how the author can feel the weight contained in Gamelan Geguntangan, and the author hopes to have the opportunity to work on a composition using Gamelan Geguntangan as a medium, but without reducing the aesthetics contained in it. Basic aesthetic properties such as unity, prominence, and balance, according to Djelantik's view, are also used as a reference to know the aesthetics of Gamelan Geguntangan apart from its weight. This study of one of the Balinese gamelan variants aims to understand Gamelan Geguntangan substantially, learning the changes in Gamelan Geguntangan and its aesthetic essence. The results obtained through this study or writing show that the aesthetics of Gamelan Geguntangan lie in one of its essential instruments, namely the Guntang instrument because the spirit of Gamelan Geguntangan lies in the instrument itself.